Czech and Dutch adjective-based similes with the animal names: an endangered species? - Křížová, Kateřina (Bohemica Olomucensia, 2019)
This article is a part of the follow-up research on the author's previous comparative research of the zooapellatives or the animal names in Dutch and Czech similes (Křížová 2017). Its aim is to point out the dynamics in this area of the phraseology and to describe some congruences and/or differences in the linguistic picture of the world, which is reflected in the Czech and Dutch adjective-based similes with the animal names. These are most often to be found in the contemporary written language. For this purpose, data from the Czech written corpora SYN2000 and SYN2015 and the Dutch corpus Corpus Hedendaags Nederlands are used.
Keywords: similes; animal names; Czech; Dutch; Corpus Hedendaags Nederlands; SYN2000; SYN2015; linguistic picture of the world